Just in time philosophy and Civil Construction: practice verification (Research, Society and Development, 2021)
Just in time is a method of rationalizing production processes, focused on efficiency, by rationally and systematically defining the production chain. Its use helps in management and decision-making, from project design to the definition of a rational layout of the construction site, in addition to the orderly planning of teams, the versatility of workers, improvement of the purchase, production, and transport processes in the execution of the work. However, not all sectors have incorporated it as they should. In this list is the civil construction sector, where there is a deficit of modernization related to proven and efficient production methods, which results in the loss of competitive advantages. In this perspective, this work aims to identify the adoption of Just in time practices in the construction of the Gama Building. For this purpose, descriptive field research was carried out, with a qualitative case study approach, with the application of an instrument with Likert scale-type questions. The results indicate that the company has not implemented JIT yet. Its use does not occur consciously and systemically by the company's management, whose managers have expertise in constructive practice, but do not have a theoretical basis to define the activities, models, and standards of the production process.